The effect of Cladophora glomerata exudates on the amino acid composition of Cladophora fracta and Rhizoclonium sp. - Pikosz Marta; Czerwik-Marcinkowska Joanna; Messyasz Beata (Open Chemistry, 2019)
Filamentous green algae (FGA) frequently forms dense mats which can be either mono- or polyspecies. While various defense mechanisms of competition in algae are known, little is known about the interactions between different species of FGA. An experiment in controlled laboratory conditions was conducted to gather data on the changes in amino acids (AA) concentrations in FGA species in the presence of exudates from different other species. The aim of the present study was to identify the AA whose concentrations showed significant changes and to assess if the changes could be adaptation to stress conditions. The major constituents of the AA pool in Cladophora glomerata, C. fracta and Rhizoclonium sp. were Glutamic acid (Glu), Aspartic acid (Asp) and Leucine (Leu). In response to chemical stress, that is the increasing presence of exudates, a significant increase in the concentrations Proline (Pro) and Tryptophan (Trp) was noted. The increase in Proline levels was observed in C. fracta and Rhizoclonium in response to chemical stress induced by C. glomerata exudates. As the concentration of exudates increased in the medium, there was a progressive shift in the pattern of AA group in FGA.